“Muntahab at-tavarih-i Мu’eeni” as a historical source - Tulibaeva Zh. М. (Journal of Oriental Studies, 2016)
Creative investigation of the rich written legacy of the past centuries has an important role in studying the history of the Kazakhs. Manuscripts in the Persian language have occupied a special place among other written sources related to Kazakh history. The purpose of this study is the identification and the systematic study of Persian manuscripts that contain important information regarding different aspects of history of Kazakhs. Included is a critical selection of the materials, their evaluation and their introduction into scientific literature.